Research on analysis model of information systems survivability - LIN Xue-gang1; XU Rong-sheng2 (Tongxin xuebao)
As information systems were open and complex,the entire problem of survivability analysis was divided into three aspects,i.e.environment,system and analysis process,and models of these aspects were given: system hierarchical model was provided based on the concept of workflow;event scenarios were used to describe the impact of environment on systems,and the environment was presented by grading event and adjusting distribution rate of the event set in different grade;based on FSM,system hierarchical state was provided,which converted the traditional direct survivability analysis based on system state into indirect hierarchical analysis.This analysis model can be applied in quantitative analysis of system survivability because of its event quantification.